Social Changes in the Development of Beef Cattle in Oil Palm Plantation Areas: Case of Jayakarta Village, Central Bengkulu Regency - Ishak, Andi; Firison, Jhon; Ramon, Erpan; Efendi, Zul; Hidayat, Taufik; Fauzi, Emlan; Putra, Wawan Eka; Wibowo, Sarwo Ferdi; Rahman, Taupik (Sodality: Jurnal Sosiologi Pedesaan, 2024)
The development of beef cattle production requires social interaction in the context of space and time. The development of beef cattle areas cannot be separated from the dynamics of social change that occur at the microlevel in the rural areas, making it interesting to study. This research aims to analyze the factors that played a role in the development of the beef cattle population in Jayakarta Village, Talang Empat Subdistrict, Central Bengkulu Regency, between 1972 and 2022. Data was collected through in-depth interviews involving key informants using the snowball method and then analyzed using an interactive method with a social change theory approach to aspects of structural and cultural change in rural communities. The research results show that the development of beef cattle is caused by the gradual production and reproduction of various cattle-rearing systems. The development of the beef cattle population is encouraged through the Government Livestock Program and the massive expansion of oil palm plantations, especially by private plantations that provide a source of cattle feed in plantation areas. Structural changes led to the formation of a semi-intensive rearing system starting in 2010 and an extensive rearing system that started in 2013, causing a change in the culture of rural community beef cattle rearing system, which was initially only intensive.